In situ investigation of the formation of Cu(In,Ga)Se-2 from selemsed metallic precursors by X-ray diffraction - The impact of Gallium, Sodium and Selenium excess - Hock, Rainer; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
The chemical reactions during rapid thermal processing of stacked elemental layers were investigated by angle-dispersive in situ X-ray diffraction. With a time resolution of 5 diffractograms per minute four different solid state reactions resulting in ternary chalcopyrites were identified: (A) CuSe + InSe -> CuInSe2, (B) Cu2Se + 2InSe + Se -> 2CuInSe(2), (C) Cu2Se + In2Se3 -> 2CuInSe(2), (D) Cu2Se + Ga2Se3 -> 2CuGaSe(2). All these reactions form pure tenary chalcopyrites. The reaction resulting in the mixed crystal Cu(In,Ga)Se-2 starts not before (B) has begun. The reaction speed of (A) and the fraction of CuInSe2 formed by (B) depend on Na-doping and Se-pressure, (C) takes place only, if the reaction paths (A) and (B) are suppressed. Reaction (D) is observed only, if 25% In is replaced by Ga in the precursor. The diffractograms were evaluated by Rietveld refinement to give the phase contents of the samples as a function of reaction time. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: chalcogenides; thin films; crystal growth; x-ray diffraction; phase transitions